Effect of gamma rays on morphological character variation of Nelumbo nucifera ‘Pathum’ - S. Soontornyatara (2018)
© 2017, International Society for Horticultural Science. All rights reserved. Nelumbo nucifera Gaertn., common name: lotus, is an aquatic plant which is widely grown in East and South-East Asian countries. Lotus flower has had only two colors, pink and white morphological characteristics for over 100 years. The major problem of this ornamental plant is its limited morphological characters for economic purposes. Thus, this project aims are to study the effect of acute gamma rays on morphological character and chromosome variation of N. nucifera cultivar ‘Pathum’. The lotus seeds were irradiated at doses of 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, and 100 Krad. The exposed seeds were cultured in plastic pots for 60 days. The results showed that the lethal dose at 50% (LD50) was 28 Krad. The 50 Krad dose or higher were lethal for seed germination. The gamma doses of 10, 20, 30 and 40 Krad produced 14, 12, 14, and 5 various abnormal characters, respectively. The morphological characters of seedlings from radiated lotus seeds were twin leaves and different types of dispersed spot leaves. The chromosome number of lotus was also studied and the results showed no difference between irradiated and control plants. The optimal radiation dose of gamma irradiation was to be around 20-30 Krad. This experiment provides basic information for N. nucifera ‘Pathum’ mutation breeding.